Optimization of Flocel 101 and Amylum as Fillers in Sambiloto (Andrographis paniculata (Burm.f.) Nees.) Capsules Formulation - Kawiyanto, Joko; Elina, Alifah Asri; Heryatman, Siti Nashwa (Jurnal Jamu Indonesia, 2024)
Sambiloto (Andrographis paniculata (Burm.f.) Nees.) is an herbal plant that is beneficial for health due to its main chemical component, andrographolide. Sambiloto can be formulated into capsules to make it more practical and comfortable for consumption, mask the bitter taste, and guarantee dosage accuracy. This research aimed to determine the optimal concentration of Flocel 101 and amylum as capsule fillers to achieve the best physical properties of Sambiloto extract capsules. The study was conducted experimentally using 5 (five) formulas (F1, F2, F3, F4, and F5) with various concentrations of Flocel 101 and amylum. A series of tests were conducted on the physical properties of the capsule powder: organoleptic tests, water content, flowability, disintegration time, and average capsule weight. Additionally, quality control was performed by checking for microbial contamination through total plate count (TPC) and yeast and mold count (YMC) tests. The results of this research indicated that the F1 formula provided the best physical properties and met the requirements, with the appearance of a greenish-gray dry powder, water content of 6.88%, flow rate of 20 g/s, disintegration time of 15.5 minutes, average weight of 0.55 g, TPC 250 cfu/g, and YMC <10 cfu/g.